Physiomechanical, Flowability, and Antibacterial Characterization of Silver-Doped Eggshell-Derived Hydroxyapatite for Biomedical Applications - Bansal G.; Gautam R.K.; Misra J.P.; Mishra A. (My University, 2025)
Hydroxyapatite (Ca10(PO4)6(OH)2, HAp), a biocompatible ceramic material, has been the priority source in several biomedical applications due to its bone type composition, crystallography and morphology. In the current research, firstly, HAp powder was synthesized from the waste eggshells using a modified synthesis route, i.e., multistage calcination preceded by a chemical precipitation method for process optimization. Secondly, the silver-doped HAp was synthesized with varying weight percent (0.0, 0.1, 0.2 and 0.5 wt.%) of silver nitrate (AgNO3) in HAp. An increase of 5.52% and 23.68% in maximum compressive strength and Vickers microhardness was observed between the undoped and 0.2 wt.% silver-doped HAp, showing the improved adhesion and bonding strength of the sintered samples. The porosity percentage also decreased with an increase in silver doping and was minimum for HAP0.2Ag (7.969%). The flowability characteristics demonstrate good flow for HAP0.0Ag (HR = 1.175 and CI = 14.89) and HAP0.1Ag (HR = 1.174 and CI = 14.87), and persists the travelable flow up to 0.5 wt.% (angle of repose = 42 ± 1.28, n = 3). Silver doping exhibits a synergistic effect, yielding satisfactory physiomechanical and antibacterial properties up to 0.2 wt.%. Inductively Coupled Plasma Mass Spectroscopy, x-ray Diffraction Technique, Fourier Transform Infrared Spectroscopy, Scanning Electron Microscopy, and Energy-Dispersive Spectroscopy verify the morphology, chemical composition, bonding strength, crystallite size, particle size, lattice strain and phase purity, respectively. Six different bacteria strains, i.e., S. epidermidis, S. aureus, B. subtilis, E. coli DH5α, P. aeruginosa and E. coli, employed for antibacterial characterization confirm the antibacterial nature of silver-doped HAp. Results obtained accentuate the antibacterial nature of silver-doped HAp and its utility in biomedical applications. Graphical Abstract: (Figure presented.). © ASM International 2023.